ASCERTAIN THE PRODUCTIVITY OF HETEROGENOUS WETLAND AND ADJACENT HABITATS THROUGH AVIAN FORAGING GUILDS - M. N. Rajpar; M. Zakaria; I. Ozdemir; S. Sheryar; A. Rab (Journal of Animal and Plant Sciences, 2018)
Birds are the most conspicuous component of wetland habitats, i.e., they are highly motile and sensitive to multitude habitat variables. Various avian species were surveyed using a distance sampling point count method and were assigned into different foraging guilds based on food selection, foraging techniques and habitat preferences. The results of foraging guilds indicated that the marsh swamp habitat was most productive, i.e., heavily utilized by avian species (i.e. 1 143.00 ± 23.86 birds ha ) and the dryland with scattered trees was less productive, i.e., less preferred by them (i.e. 65.03 1 1 ± 9.79 birds ha ). Overall, guild Frugivore/Insectivore birds were the most dominant (149.89 ± 20.25 birds ha ) and 1 Carnivore ( 0.40 ± 0.19 birds ha ) were less abundant in five habitats. Likewise, resident birds were the most dominant in each habitat and vagrant birds were rarely observed. For migrant bird, guild Insectivore was the most dominant in five 1 1 habitats such as marsh swamp; 1.24 ± 0.08 birds ha , lotus swamp; 1.28 ± 0.32 birds ha , open water body; 0.74 ± 0.12 1 1 1 birds ha , dryland with scattered trees; 2.05 ± 0.20 birds ha and scrubland; 1.44 ± 0.15 birds ha . The findings of foraging guilds indicated that birds are specialize in food selection, i.e., foraged on a wide array of animals through employing various foraging techniques to catch their prey and select the available wetland and adjacent habitats in different ways depending on availability of food resources, foraging behaviour and niche. Hence, birds are bio-indicators of wetland and adjacent habitats and can be ascertained the productivity (health) of the particular habitat. may exploit the same foraging sites, same food resources,
Keywords: Foraging guild; Marsh Swamp; Bird; Migrant; Residents; Scrubland.